ANALISIS KOMPONEN UTAMA (AKU) UNTUK PENGELOMPOKAN AREA PELAYANAN DAN JARINGAN (APJ) DAERAH JAWA TENGAH DAN D.I. YOGYAKARTA - Safaat Yulianto; Ully Putriana (Institut Teknologi Statistika dan Bisnis Muhammadiyah Semarang, 2020)
Principal component analysis is a statistical analysis of multiple variables that can be used to reduce the number of original variables into new variables that are orthogonal and keep the total variability of the original variables. This study will classify each APJ in Central Java and Yogyakarta based on the factors that influence it. The data used is the Data and Statistics Year 2010 issued by PT. PLN (Persero) Distribution Central Java and D.I. Yogyakarta.